Acute pancreatitis and COVID-19: a new target for infection? - Balthazar,Júlia Aith (2022)
ABSTRACT This review aimed to investigate whether SARS-CoV-2 is capable of infecting the gland and causing acute pancreatitis, and the peculiarities in the management of these cases. The research was conducted through PubMed® database, and 62 articles were systematically selected for analysis. Differences were found in the literature; however, there are important warnings, such as the presence of hyperlipasemia, clinical and imaging findings suggestive of acute pancreatitis in the presence and even in the absence of respiratory symptoms. Attention should be paid to clinical and imaging findings during this virus infection, since it is possible to identify these two diseases early. Therefore, it is possible to detect and isolate these patients more quickly, providing the correct care and decreasing the morbidity and mortality of two potentially severe diseases.